2023
DOI: 10.3389/fnut.2023.1129548
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-binding properties, stability, and osteogenic ability of phosphorylated soy peptide-calcium chelate

Abstract: IntroductionBioactive peptides based on foodstuffs are of particular interest as carriers for calcium delivery due to their safety and high activity. The phosphorylated peptide has been shown to enhance calcium absorption and bone formation.MethodA novel complex of peptide phosphorylation modification derived from soybean protein was introduced, and the mechanism, stability, and osteogenic differentiation bioactivity of the peptide with or without calcium were studied.ResultThe calcium-binding capacity of phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Additionally, the absorption intensity increased from 2.146 to 2.253. The increased absorption intensity could potentially stem from changes in the electronic cloud of the amide bond and the light absorption characteristics of the ligand caused by binding to Ca 2+ as reflected in the results of quantum chemistry. Wang et al found that the absorption band intensity of purified peptide–calcium complex FVDVT-Ca significantly increased .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the absorption intensity increased from 2.146 to 2.253. The increased absorption intensity could potentially stem from changes in the electronic cloud of the amide bond and the light absorption characteristics of the ligand caused by binding to Ca 2+ as reflected in the results of quantum chemistry. Wang et al found that the absorption band intensity of purified peptide–calcium complex FVDVT-Ca significantly increased .…”
Section: Resultsmentioning
confidence: 99%
“…The content of acidic amino acids in bioactive peptides is closely related to their calcium ion binding ability. 30 Therefore, in this experiment, the top 10 peptide segments containing a minimum of three acidic amino acids and with the highest abundance in RPP (LEKPEGADLE, LIEKHEGGLEE, IE-KHEGGLEE, VAGSAPGIEGDEIAPL, LTESQSQSHKFK-DEHQ, RVDEDREEL, LEEQKGSDVM, EVEERSQNIFSG, AHVGMSGEEPE and ISGFEGDNMIER) were chosen as the receptor and ligand for molecular docking with Ca 2+ (Figure 1A and Supporting Figure 1). The length of these peptides ranged from 9 to 16 amino acids, and their mass ranged from 1100 to 2057 Da (Table 1).…”
Section: Peptide Sequence Identification and Selectionmentioning
confidence: 99%